2009
DOI: 10.3168/jds.2008-1906
|View full text |Cite
|
Sign up to set email alerts
|

The effect of floor surface on dairy cow immune function and locomotion score

Abstract: This study evaluated the effect of 2 dairy cow housing systems on cow locomotion, immune status, and expression of genes associated with lameness during the dry and periparturient periods. Cows were assigned to freestall housing with either rubber (RUB; n = 13) or concrete (CON; n = 14) at the feed-bunk and alley immediately after their first calving, and managed on this system during all subsequent lactations. At dry off, cows were moved to a straw bedded-pack dry cow pen, and remained there until about 2 d b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…Although the reason behind such high variability is not clear, there is evidence that the stress and/or health status of each animal impacts on their immune cell profile [32]. In contrast to the findings of Cobb and Watson [9], our results did not show any evidence of estrous cycle regulation of total endometrial CD4 + or CD8 + cell numbers, nor a preponderance of CD8 + cells in the luminal epithelium.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the reason behind such high variability is not clear, there is evidence that the stress and/or health status of each animal impacts on their immune cell profile [32]. In contrast to the findings of Cobb and Watson [9], our results did not show any evidence of estrous cycle regulation of total endometrial CD4 + or CD8 + cell numbers, nor a preponderance of CD8 + cells in the luminal epithelium.…”
Section: Discussioncontrasting
confidence: 99%
“…This type of leukogram is seen in all vertebrate taxa in response to either natural stressors, or administration of stress hormones (Davis et al, 2008). A high N:L ratio has also been described in animals in stressful circumstances (Fell et al, 1999), in cows that are genetically more susceptible to disease (Kulberg et al, 2002), and in cows with poor locomotion (O'Driscoll et al, 2009). Thus this leukocyte profile is in concordance with the elevated cortisol levels we detected in cows with ulcers.…”
Section: Discussionsupporting
confidence: 77%
“…Not only has MMP-13 mRNA been observed to be up-regulated in the leukocytes of clinically lame cows, when using both a micro-array and targeted gene expression approach (Almeida et al, 2007), but O'Driscoll et al (2009) found that even in cows that weren't clinically lame, but with impaired locomotion, leukocytes MMP-13 mRNA was up-regulated. Matrix metalloproteinases (MMPs) are involved in extracellular protein degradation, with MMP-13 also known as collagenase 3, due to its role in collagen degradation (Entrezgene, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some peripheral immune cell responses seem to have indicators of both pain and the repair process (Almeida et al, 2007). Recent data from our laboratory shows that a painrelated gene (tachykinin 1, TAC1) as well as a gene involved in cartilage tissue repair (metalloproteinase-13) changed around parturition for cows that had been housed on rubber rather than concrete (O'Driscoll et al, 2009). Therefore, our objectives for this study were to determine the health, cow comfort, hoof health, and leukocyte gene expression of cows housed on rubber flooring compared with those on only concrete.…”
Section: Introductionmentioning
confidence: 97%